2014
DOI: 10.1108/jocm-02-2014-0025
|View full text |Cite
|
Sign up to set email alerts
|

Employee loyalty and organizational performance: a critical survey

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 72 publications
2
75
0
6
Order By: Relevance
“…However, some of the researchers identify two basic approaches to determine employee loyalty, namely: the attitudinal approach, and the behavioral approach. From attitudinal perspective, loyalty refers to an individual's psychological inclinations, feelings, identification, attachment or commitment to the organization [31,32]. However, the cognitive nature of attitudinal approach makes the measurement of loyalty difficult and questionable [31,33,34].…”
Section: Employee Loyalty (El)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, some of the researchers identify two basic approaches to determine employee loyalty, namely: the attitudinal approach, and the behavioral approach. From attitudinal perspective, loyalty refers to an individual's psychological inclinations, feelings, identification, attachment or commitment to the organization [31,32]. However, the cognitive nature of attitudinal approach makes the measurement of loyalty difficult and questionable [31,33,34].…”
Section: Employee Loyalty (El)mentioning
confidence: 99%
“…From attitudinal perspective, loyalty refers to an individual's psychological inclinations, feelings, identification, attachment or commitment to the organization [31,32]. However, the cognitive nature of attitudinal approach makes the measurement of loyalty difficult and questionable [31,33,34]. Whereas, behavioral approaches view loyalty as an observable phenomenon that is obvious and can be easily materialized in the context of employee-organization relationships [35,36].…”
Section: Employee Loyalty (El)mentioning
confidence: 99%
“…On the other hand the industry does not focus on long-term relationship (McPhail and Fisher, 2008), which impact on building workers' loyalty to the organization. Guillon and Cezanne (2014) have observed that over investment in creating employee loyalty might lead to high turnover. Loyalty to organisation may become dysfunctional, even more so when workers' loyalty to the organization is not reciprocated (Guillon and Cezanne, 2014).…”
Section: H7: There Is a Negative Linear Relationship Between Employeementioning
confidence: 99%
“…Guillon and Cezanne (2014) have observed that over investment in creating employee loyalty might lead to high turnover. Loyalty to organisation may become dysfunctional, even more so when workers' loyalty to the organization is not reciprocated (Guillon and Cezanne, 2014). High levels of loyalty are not enough in retaining employees working in a turnover culture environment Then, knowing that high levels of loyalty are not enough to avoid turnover as well as may become dysfunctional in an organisation, a quadratic relationship could be explored, where higher levels of loyalty may also increase worker's' intention of turnover.…”
Section: H7: There Is a Negative Linear Relationship Between Employeementioning
confidence: 99%
“…The main concern of this research study is to evaluate the effectiveness of loyal employees towards their jobs and organizations. Now employee loyalty has gone beyond than being a hypothetical construct (Guillon & Cezanne, 2014).…”
Section: Introductionmentioning
confidence: 99%